Follow-up care for premature children: the repercussions of the COVID-19 pandemic - Rosane Meire Munhak da Silva; Letícia Pancieri; Adriana Zilly; Fabiana Aparecida Spohr; Luciana Mara Monti Fonseca; Débora Falleiros de Mello (Universidade de São Paulo, 2021)
Objective: to analyze elements of the follow-up care provided to premature children amidst the COVID-19 pandemic. Method: qualitative study from the perspective of philosophical hermeneutics, interpreting experiences with childcare provided at home. Twelve mothers and 14 children aged two years old were interviewed online via a text messaging application. Data were analyzed by interpreting meanings. Results: weaknesses stood out in the follow-up care provided to children such as gaps of communication, lack of guidance and delayed immunizations, while care intended to meet health demands was interrupted. Vulnerability aspects affecting child development included: social isolation measures that impeded the children from socializing with their peers, increased screen time, the manifestation of demanding behaviors and irritation and the mothers experiencing an overload of responsibilities. The elements that strengthened maternal care included the mothers being attentive to contagion, enjoying greater experience and satisfaction with the maternal role, spending more time with their children, and recognizing respiratory signs and symptoms, especially fever. Conclusion: follow-up care provided to children in stressful situations implies implementing practices that support the wellbeing of children and families, decreasing the likelihood of children being exposed to development deficits, and detecting signs and symptoms timely. The use of nursing call centers can break the invisibility of longitudinal needs and promote health education actions at home.